2017
DOI: 10.1039/c7ra02937c
|View full text |Cite
|
Sign up to set email alerts
|

Top-down fabrication of fluorine-doped tin oxide nanopillar substrates for solar water splitting

Abstract: Nanopillar fluorine-doped tin oxide (FTO) substrates fabricated by nanosphere lithography and argon milling enhance the photoelectrochemical performance of WO3 photoanodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Figure S4 shows additional voltammograms at varying scan rates. The capacitive charging is proven by a linear dependence of the voltammetric current, j DL , in the “double-layer” region (at −0.1 V) on the scan rate, v (Figure A, inset): Equation gives the Helmholtz capacitance of a blank FTO of C H ≈ 30 μF/cm 2 (Table S2), which is comparable to the values reported by others (15–50 μF/cm 2 ). , The corresponding capacitance of CuSCN is significantly larger, C H ≈ 130 μF/cm 2 . We may note that the CuSCN films were reported to have quite high specific capacitances from 17 to 760 F/g in a potential region from −1 to 1 V .…”
Section: Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Figure S4 shows additional voltammograms at varying scan rates. The capacitive charging is proven by a linear dependence of the voltammetric current, j DL , in the “double-layer” region (at −0.1 V) on the scan rate, v (Figure A, inset): Equation gives the Helmholtz capacitance of a blank FTO of C H ≈ 30 μF/cm 2 (Table S2), which is comparable to the values reported by others (15–50 μF/cm 2 ). , The corresponding capacitance of CuSCN is significantly larger, C H ≈ 130 μF/cm 2 . We may note that the CuSCN films were reported to have quite high specific capacitances from 17 to 760 F/g in a potential region from −1 to 1 V .…”
Section: Results and Discussionsupporting
confidence: 79%
“…Equation 4 gives the Helmholtz capacitance of a blank FTO of C H ≈ 30 μF/cm 2 (Table S2), which is comparable to the values reported by others (15−50 μF/cm 2 ). 13,21 The corresponding capacitance of CuSCN is significantly larger, C H ≈ 130 μF/cm 2 . We may note that the CuSCN films were reported to have quite high specific capacitances from 17 to 760 F/g in a potential region from −1 to 1 V. 22 However, considering the complicated electrochemistry of CuSCN (Figure 1), these capacitances may include various faradaic or pseudo-faradaic components.…”
Section: Resultsmentioning
confidence: 99%
“… 102 High-performance PEC modules could rely on scarce elements such as gallium, arsenic, cadmium, and tellurium for light absorption. 23 The conductivity of the glass electrodes relies on transparent conducting oxides made from tin 106 or indium, 107 which is a similar materials constraint for flexible organic PV modules 108 compared to silicon PV modules. Recycling is important for mitigating materials depletion, as has been explored for electronics waste, 109 but the available data on recycling PV-E and PEC components is extremely limited.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Müller et al reported an increase in the charge transfer efficiency of 88% when an inverse opal WO 3 scaffold was spin-coated with Sn-doped α-Fe 2 O 3 . In the same line, antimony-doped tin oxide and indium-doped tin oxide inverse opals were also employed as scaffolds rendering similar results. A recent report from Jaramillo’s group exhibited a template-assisted ion milling technique for the top-down formation of nanopillars on commercial fluorine-doped tin oxide (FTO) samples providing a 40% enhancement of the final photocurrents when compared to the planar counterpart in WO 3 photoanodes deposited by atomic layer deposition (ALD) . Although this work represents a very promising proof of concept, the relatively low aspect ratio of the nanopillars (roughness factor was 1.4 times over native FTO) in the resulting scaffold and the complexity of the milling process are the main drawbacks of this top-down approach.…”
Section: Introductionmentioning
confidence: 81%
“…1517 A recent report from Jaramillo’s group exhibited a template-assisted ion milling technique for the top-down formation of nanopillars on commercial fluorine-doped tin oxide (FTO) samples providing a 40% enhancement of the final photocurrents when compared to the planar counterpart in WO 3 photoanodes deposited by atomic layer deposition (ALD). 18 Although this work represents a very promising proof of concept, the relatively low aspect ratio of the nanopillars (roughness factor was 1.4 times over native FTO) in the resulting scaffold and the complexity of the milling process are the main drawbacks of this top-down approach.…”
Section: Introductionmentioning
confidence: 96%